PEMANFATAN DESTINASI WISATA BUMI PERKEMAHAN NGROWO BENING SEBAGAI SUMBER BELAJAR IPS PADA SISWA KELAS V SDN 01 MANISREJO KOTA MADIUN - Suharsi - Suharsi; Sudarmiani - Sudarmiani; Nurhadji - Nugraha (STKIP PGRI TULUNGAGUNG, 2022)
This study aims to describe the utilization of the Ngrowo Bening campground tourism destinations as a social science learning resource for fifth grade students of SDN 01 Manisrejo Madiun City. The research method used is qualitative descriptive . (Poerwandari, 2005), qualitative research produces and rejects descriptive data. Data collection techniques using observation, in-depth interviews, questionnaires, and documentation. Data analysis using analysis techniques from Miles and Huberman: data collection, data reduction, data presentation, and conclusion / verification The results showed that the camping ground of Ngrowo Bening tourism destination was feasible to be used as a social science learning resource for the fifth grade students of SDN 01 Manisrejo, Madiun City. Based on the research results: (1) learning activities are more interesting and less boring; (2) the nature of learning will be more meaningful, students are exposed to actual situations and conditions; (3) materials that can be studied are richer and factual; (4) student learning activities are more comprehensive and more active, students can observe, ask, prove or demonstrate, test facts; and (5) learning resources are richer, because they are diverse, such as the social environment, nature, and so on.